Determinação de nimodipino em plasma humano através de cromatografia líquida de alta eficiência acoplada à espectrometria de massa (LC-MS-MS) - Nascimento, Demétrius Fernandes do (2005)
A rapid, specific and highly sensitive liquid chromatography-tandem mass spectrometry method was developed to determine nimodipine in human plasma using dibucaine as the internal standard (IS) is described. The analyte (m/z 418,6 > 342,6) and IS (m/z 344,2 > 271,0) were extracted from plasma samples by liquid-liquid extraction using hexane-ethyl acetate (1:1v/v). Chromatography was performed on a Varian® Polaris C18 analytical column (3 micrometer, 50 x 2,0 mm) and pre-column SecurityguardTM C18 (4,0 x 3,0 mm). The phase mobile consisted of Acetonitrile-Ammonium acetate 0.02 ml/L (80:20v/v). The method had a chromatographic run time of 4.5 min and linear calibration curve over the range 0.1- 40 ng/mL (r2 > 0.9938). The limit of quantification (LQ) was 0.1 ng/mL. The intra-day precision for the limit quantification was 0.00% (batch 01), 5.71% (batch 02) and 5.27% (batch 03); for the quality controls low (QCL), middle (QCM) and high (QCH) the results were respectively 8.57, 0.81 and 1.37%. The inter-day precision for LQ and QCL, QCM and QCH were respectively: 7% and 5.46, 4.12 and 3.37%. The intra-day accuracy for LQ was 110, 96 and 104%; for QCL, QCM and QCH the results were100.67, 109.09 and 109.72% respectively. The results of the inter-day accuracy for LQ, QCL, QCM and QCH were respectively and 110.0, 96.0, 104.0% for the limit of quantification and 8.57, 0.81, 1.37% and 100.67, 109.09, 109.72% respectively: 103% e 102.89, 106.60, 109.69%. This validated method was successfully applied for the pharmacokinetic profiles of nimodipine tablets administered to 24 healthy volunteer’s participant of bioavailability comparative study. Geometric mean of Test formulation/Refernce formulation individual percent ratio was 104,56% for AUC0-48h and 55,73% for Cmax. The 90% for the confidence intervals (CI) were 94,80-115,32% e 44,73-69,42%, respectively. The values of half-life and Cmax for test formulation and reference formulation were 27,83;32,78h and 9,48;18,76ng/mL, respectively. The values of Tmax were 2,34;0,98h for the formulations test and reference respectively. Since the 90% CI for Cmax and AUC0-48h, were within the 80-125% interval proposed by the “Food and Drug Administration” and ANVISA, it was concluded that the two formulations of nimodipine 30mg tablets were not bioequivalent, according to the rate of absorption after single dose administration.